An Ethical Frame for Research with Immigrant Families. Issue 141 (3rd September 2013) - Nguyen, Jacqueline; Hernández, María G.; Saetermoe, Carrie L.; Suárez‐Orozco, Carola
Abstract: In this introduction, the editors give an overview of the ways the volume addresses the growing individual and institutional calls for increased clarity and rigor in methodological, ethical, and practical research policies and guidelines for conducting research with immigrant individuals, families, and communities. In addition to summarizing the volume's purpose, background on the U.S. immigrant population is given, followed by delineation of the five major issues contributing to the field of immigrant studies research and entering the "field" and engaging with immigrant families and communities: heterogeneity and history, documentation status, research pragmatics, research lens and bias, and influence on policy. © 2013 Wiley Periodicals, Inc.